State history, historical legitimacy and modern ethnic diversity - Bleaney, Michael; Dimico, Arcangelo (Elsevier, 2016)
How much does the antiquity of states, and the sometimes arbitrary nature of colonial boundaries, explain the modern degree of theory of ethnic diversity and income disthnic diversity? It is shown that states with greater historical legitimacy (more continuity between the pre-colonial and post-colonial state) have less ethnic diversity. Historical legitimacy is more strongly correlated with ethnic diversity than the antiquity of states, genetic diversity or the duration of human settlement. Although historical legitimacy is particularly pertinent to Africa, the correlation also holds outside Africa.